2000
DOI: 10.1055/s-2000-12065
|View full text |Cite
|
Sign up to set email alerts
|

Early Biliary Pseudolithiasis During Ceftriaxone Therapy for Acute Pyelonephritis in Children: A Prospective Study in 34 Children

Abstract: The prolonged biological half-life of Ceftriaxone, allowing once-daily dosing, has contributed to the large diffusion of this third-generation cephalosporin in children. Ceftriaxone is known to induce reversible precipitates in the gallbladder of adults and children. A prospective study was conducted during 1997 in 34 children admitted for the treatment of acute pyelonephritis. Ceftriaxone (intravenous daily single-dose of 50 mg/kg under 2g/day) was initially used. A first gallbladder sonogram, performed befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 0 publications
0
24
1
Order By: Relevance
“…These biochemical characteristics of ceftriaxone treatment frequently cause biliary sludge or pseudolithiasis, a well-known side effect in children [2][3][4][5]. This complication may develop after 2-16 days of treatment initiation [4-6, 13, 14] and is characterized by asymptomatic biliary changes; in most cases, it is reversible [3,13]. Prospective studies have revealed that the incidence of pseudolithiasis is 25-50% in children being treated with ceftriaxone [2,3,15].…”
Section: Discussionmentioning
confidence: 99%
“…These biochemical characteristics of ceftriaxone treatment frequently cause biliary sludge or pseudolithiasis, a well-known side effect in children [2][3][4][5]. This complication may develop after 2-16 days of treatment initiation [4-6, 13, 14] and is characterized by asymptomatic biliary changes; in most cases, it is reversible [3,13]. Prospective studies have revealed that the incidence of pseudolithiasis is 25-50% in children being treated with ceftriaxone [2,3,15].…”
Section: Discussionmentioning
confidence: 99%
“…The longest time interval i.e. 5 months of resolution of sludge was reported by Bonnet et al 13 . In the present study comparison was made between the biliary sludge formation group and normal group ( Table-II).…”
Section: Discussionmentioning
confidence: 88%
“…Taking into account these higher concentrations of ceftriaxone and calcium, and the stasis in the urinary bladder as well as in the gallbladder, it is comprehensible why renal and biliary lithiasis emerges. 18,[41][42][43][44][45] Therefore, biliary precipitation and nephrolithiasis limit the C max that can be achieved in vivo.…”
Section: Discussionmentioning
confidence: 99%